1996
DOI: 10.1212/wnl.47.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolactin concentrations are elevated after syncope

Abstract: S ince the initial paper by Trimble in 1978 1 highlighting postictal levels of serum prolactin as a way to separate epileptic from nonepileptic seizures, PubMed has logged approximately 300 articles retrievable by the search terms "epilepsy" and "prolactin." Despite this considerable body of work, the role of serum prolactin in diagnosis of seizures remains uncertain. In this issue of Neurology ® Clinical Practice, Abubakr and Wambacq 2 evaluated serum prolactin levels 20 minutes after a behavioral seizure-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Psychogenic or physiologic nonepileptic events also can influence serum PRL level. Several studies [7][8][9][10] have suggested that serum PRL can increase after syncope, a common imitator of epilepsy.Recent interest in the use of PRL has diminished …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Psychogenic or physiologic nonepileptic events also can influence serum PRL level. Several studies [7][8][9][10] have suggested that serum PRL can increase after syncope, a common imitator of epilepsy.Recent interest in the use of PRL has diminished …”
mentioning
confidence: 99%
“…(table 4). In one study of subjects with a mean age of 70 years, 7 11 syncopal subjects showed an elevated mean PRL level of 44 ng/mL (95% CI 27 to 61) when tested within 5 minutes of syncope, compared with a mean baseline PRL level of 10 ng/mL (95% CI 7 to 14). Ten nonsyncopal subjects showed no significant PRL change following head-up tilt.…”
mentioning
confidence: 99%
“…Again consistent with other studies, our results showed that serum PRL levels did not help diff erentiate epilepsies and syncopes. In these studies, Oribe et al (16) showed that serum PRL levels were as high as those seen in epilepsies in 21 patients in whom they induced syncopes with tilt test. Leuf (15) showed that PRL was not helpful in diff erentiation of epileptic seizure and syncope; and fi nally Chen et al (14) showed that serum PRL levels were not helpful in diff erentiating epileptic seizure and syncope.…”
Section: Discussionmentioning
confidence: 96%
“…However, as a distinguishing feature hyperprolactinemia can be seen in either seizure or syncope. Oribe performed a tilt table analysis with 11 of 21 patients demonstrating a four fold rise in PRL (9-52 ng/ml), while it remained unchanged in those without tilt induced syncope [8].…”
Section: Discussionmentioning
confidence: 99%